1970
DOI: 10.1128/aem.19.4.681-688.1970
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a New Strain of Bacillus popilliae Sporogenic In Vitro

Abstract: Conditions are described that led to the isolation of NRRL B-2309M, a strain of Bacillus popilliae which sporulates regularly in laboratory culture. Colonies grown on a medium formulated with yeast extract and the ingredients of Mueller-Hinton with phosphate, trehalose, and agar, produced 20% spores in 10 to 12 days. The quantity and kind of yeast extract determine the extent of sporulation, although there are other requirements for optimal growth and sporulation. Spore inocula free of viable vegetative cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…There was, however, a secondary growth response after some apparent cell lysis. I incubated These observations correlate well with those of ,mples were Sharpe et al (22). They observed that the spores me medium in the colonies were found in a concentric ring i rates were near the outer edge of the colony surrounded by iuired for a vegetative cells and prespore forms in the outer at-resistant fringe.…”
Section: (29%)supporting
confidence: 84%
See 2 more Smart Citations
“…There was, however, a secondary growth response after some apparent cell lysis. I incubated These observations correlate well with those of ,mples were Sharpe et al (22). They observed that the spores me medium in the colonies were found in a concentric ring i rates were near the outer edge of the colony surrounded by iuired for a vegetative cells and prespore forms in the outer at-resistant fringe.…”
Section: (29%)supporting
confidence: 84%
“…We have never been able to achieve the frequency of spore formation by B. popilliae strain 2309M in vitro as reported by Sharpe et al (22).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Subculturing of the organism during spore production or strain maintenance may introduce the opportunity for the accumulation of genetic changes. Phenotypic variants of NRRL B-2309 have arisen in the past (16,18), and it is possible that previously undetected genetic changes have accumulated in various laboratories.…”
mentioning
confidence: 99%
“…Large-scale fermentative production of infective spores of Bacillus popilliae Dutky would supply a proven biological insecticide (3,14) to control the Japanese beetle, Popillia japonica Newman. Suitable vegetative proliferation of this entomopathogen has been reported (9), and methods for obtaining limited sporulation in liquid and on solid medium have been described (5,10,15). Nevertheless, a means to induce extensive sporulation of B. popilliae growing in laboratory media has evaded discovery.…”
mentioning
confidence: 99%